Comparative Analysis of Implant Survival and Clinical Efficacy between Medial and Lateral Unicompartmental Knee Arthroplasty: A Systematic Review and Meta-Analysis - Zhang, Tao; Li, Wenwen; Wu, Dan; Ying, Jinghe; Chen, Jianlong; Rastogi, Sanjay (The Journal of Knee Surgery, 2025)
Unicompartmental knee arthroplasty (UKA), encompassing both medial and lateral approaches, facilitates accelerated rehabilitation and enhances patient satisfaction in comparison to total knee arthroplasty (TKA). However, the optimal surgical techniques and implant positioning continue to be topics of ongoing debate. This study compares the clinical efficacy and implant survival rates of medial and lateral UKA to inform clinical decision-making and optimize patient outcomes. A comprehensive literature search was performed across four major electronic databases (PubMed, EMBASE, Scopus, and Cochrane Library), yielding peer-reviewed journal articles that met the inclusion criteria. Statistical analysis involved calculating standardized mean differences (SMDs) and odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Heterogeneity was evaluated using the Cochrane Q test and I2 statistic, with p-values reported accordingly. Data analysis was facilitated using Review Manager (RevMan) version 5.4. This meta-analysis of 15 studies (n = 36,006 UKA patients) found no significant differences in survival rates, postoperative pain, and function scores between medial and lateral UKA. Specifically, the long-term subgroup (>10 years) showed a non-significant higher survival rate for lateral UKA (OR: 0.99, 95% CI: 0.73–1.32, p = 0.92, I2 = 51%), while the short- and mid-term subgroup (<10 years) showed a non-significant higher survival rate for medial UKA (OR: 1.20, 95% CI: 0.96–1.50, p = 0.12, I2 = 73%). Additionally, the pooled SMD revealed no significant differences in postoperative pain (SMD: 0.08, 95% CI: −0.27 to 0.44) and functional scores (SMD: 0.23, 95% CI: −0.05 to 0.51) between the two groups. In conclusion, this systematic review and meta-analysis found no substantial disparities in clinical outcomes, survival rates, functional improvement, or pain alleviation between medial and lateral UKAs, confirming both as viable options.
Keywords: knee osteoarthritis; unicondylar knee replacement; unicompartmental knee arthroplasty (medial/lateral); implant survival; all-polythene prosthetics; metal-backed prosthetics; pain score; functional score